2019
DOI: 10.1074/mcp.ra119.001455
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effect of Deuterium Depleted Water - Redox Disbalance Leads to Oxidative Stress

Abstract: The antiproliferation effect of deuterium depleted water (DDW) is well documented, but the mechanism remained elusive. Here three complementary proteomics approaches applied to A549 cells revealed a disbalance brought about by DDW in mitochondria between ROS production and neutralization, thus leading to oxidative stress in the cells. Subsequent validation by orthogonal approaches supported this scenario. Therefore, DDW has potential as an adjuvant in antitumor therapy, especially in the modalities inducing ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 59 publications
2
44
0
Order By: Relevance
“…Flow cytometry for CD4 + T cell and platelet phenotyping, 19 mass spectrometry, 24 confocal microscopy, 25,26 and western blotting 25,26 used in the present study have been described previously. These methodologies have been detailed in Appendix S1.…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometry for CD4 + T cell and platelet phenotyping, 19 mass spectrometry, 24 confocal microscopy, 25,26 and western blotting 25,26 used in the present study have been described previously. These methodologies have been detailed in Appendix S1.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it was shown that a decrease in the deuterium content in the blood and brain of laboratory animals reduces the disruption of antioxidant enzymes functioning during hypoxia in comparison with animals that received water with a natural deuterium content [ 17 ]. The administration of water with a reduced deuterium content into the drinking diet leads to a change in the 2 H/ 1 H ratio in the body tissues due to the hydrogen isotopes exchange [ 18 ], in particular, as shown by the recent study, the antiproliferation effects of DDW are associated with the occurrence of an imbalance in the mitochondria between the production of reactive oxygen species and their neutralization [ 19 ]. Some studies have shown an increase in H 2 O 2 production by mitochondria during their pre-incubation in the deuterium depleted media [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several works [65,66,67,68,69,70] indicate the multidirectional effect of isotope exchange reactions on the functional activity of biological systems, their native properties, and structural organization. Nevertheless, most bioeffects associated with changes in the isotope composition of biogenic elements in the body are still not fully understood [71], which primarily concern the effect of low (compared to the natural level) concentrations of heavy nonradioactive isotopes on living systems.…”
Section: In Vivo 2h/1h Exchange Effectsmentioning
confidence: 99%
“…Using knowledge of isotope resonance through the BADz phenomenon will also allow more efficient poly-isotope correction of metabolic disorders in various diseases by creating conditions for targeted fractionations of isotopes in certain pathological cells and certain focuses of the disease. The latter is relevant because in current medical practice, increasing numbers of different metabolic disorders and cell pathologies are corrected by mostly monoisotopic medicines, especially 2 H-isotope-modified drinking and diet therapies in healing the following diseases and certain conditions: Alzheimer’s disease was treated by deuterium-reinforced polyunsaturated fatty acids (D-PUFAs), which improved cognition in mice fed a Western-type diet [117], and reduced the brain tissue concentrations of oxidation products and amyloid β-peptide in APP/PS1 mutant transgenic mice [118]; Parkinson’s disease was partially cured by the administration of D-PUFAs, which protected against nigrostriatal damage (in the substantia nigra) from oxidative injury in mice with a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine model [119];Mitochondrial disorders and oxidative stress were corrected by both deuterium-depleted water [16,55,56,65,69,120,121] and D-PUFAs, such as 11,11-D(2)-linoleic and 11,11,14,14-D(4)-α-linolenic acids and others, which preserved mitochondrial bioenergetics function under toxic effects of t -butylhydroperoxide, ethacrynic acid, or ferrous iron [122], prevented coenzyme Q (ubiquinone or CoQ)-less coq mutants and some toxic effects of lipid autoxidation products [123,124,125], and also decelerated the aging process by deuterated trilinolenin (D-TG (54:9)), resulting in extended lifespan of worms under normal and oxidative stress conditions [126];Cerebral hypoxia was corrected by deuterium-depleted water, the long-term consumption of which resulted in activation of neuron protective systems, with higher antioxidant activity in brain tissues [68,75];Friedreich’s ataxia was treated by deuterated linoleic and α-linolenic acids, which resulted in rescue of oxidative-stress-challenged cells by decreasing lipid peroxidation [127], and also deuterated ethyl linoleate (RT001), which recovered mitochondrial function [128];Huntington’s disease was managed by D-PUFA diet in Q140 knock-in mice, which were able to demonstrate improved performance in novel object recognition tests after 5 months of consumption of deuterium-enriched diet [129];Cancer adjuvant therapy showed efficacy through the administration of 1 H 2 O [22,70,130,131], and previously-drug-processed gliomas was treated by combining deuterium...…”
Section: Possibility Of Using the Isotopic Therapy In 2h-modified mentioning
confidence: 99%
See 1 more Smart Citation